Valganciclovir Dosing for Cytomegalovirus Prophylaxis in Solid-organ Transplant Recipients on Continuous Veno-venous Hemodialysis. (7th May 2020) - Jarrell, Andrew S; Crow, Jessica R; Strout, Sara E; Kruer, Rachel M; Toman, Lindsey P; Dioverti-Prono, Maria V; Lees, Laura; Avery, Robin K; Marzinke, Mark A
Abstract: Background: Optimal valganciclovir dosing for cytomegalovirus (CMV) prophylaxis in solid-organ transplant (SOT) patients on continuous veno-venous hemodialysis (CVVHD) is not known. Ganciclovir trough concentrations ≥0.60 μg/mL have been suggested for CMV prophylaxis. This study was conducted to determine if valganciclovir 450 mg enterally every 24 hours achieves ganciclovir trough concentrations ≥0.60 μg/mL in patients on CVVHD. Methods: This single-center, prospective, open-label, pharmacokinetic study included adult SOT patients admitted to an intensive care unit from March 2018 to June 2019 on CVVHD. All patients were receiving valganciclovir 450 mg enterally every 24 hours for CMV prophylaxis prior to enrollment. Each patient had a peak and trough sample drawn at steady state. Results: Ten SOT patients were included in the study (6 liver, 1 simultaneous liver-kidney, 2 bilateral lung, 1 heart). The mean ± SD age was 51.8 ± 14.0 years, and average body mass index was 27 ± 6.9 kg/m 2 . Ganciclovir trough concentrations ranged from 0.31 to 3.16 μg/mL, and 80% of participants have trough concentrations ≥0.60 μg/mL. No patients had documented neutropenia while on valganciclovir and CVVHD; 60% of patients had significant thrombocytopenia. Conclusions: Valganciclovir 450 mg enterally every 24 hours achieved ganciclovir trough concentrations ≥0.60 μg/mL in most patients on CVVHD, similar to those reported with intravenous ganciclovir for prophylaxis in this population. Based on these data, valganciclovir may require dosing every 24 hours to achieve concentrations equivalent to ganciclovir. Neutropenia did not occur in the study period. Thrombocytopenia was common and likely multifactorial. Abstract : The pharmacokinetics of valganciclovir for cytomegalovirus prophylaxis were evaluated among solid-organ transplant patients receiving continuous veno-venous hemodialysis. Valganciclovir 450 mg enterally every 24 hours effectively achieved target valganciclovir trough concentrations. Thrombocytopenia was common and multifactorial; neutropenia did not occur.